Health risk assessment of aflatoxin M1 in infant formula milk in IR Iran. (August 2020) - Hooshfar, Shirin; Khosrokhavar, Roya; Yazdanpanah, Hassan; Eslamizad, Samira; Kobarfard, Farzad; Nazari, Firouzeh; Kokaraki, Venetia; Kokkinakis, Manolis; Goumenou, Marina; Tsitsimpikou, Christina; Tsatsakis, Aristides
Abstract: In this study, two accurate, precise, selective and sensitive methods were developed for determining aflatoxin M1 (AFM1) in infant formula milk using immunoaffinity column clean-up followed by high performance liquid chromatography (HPLC) with fluorescence detection. The validated methods were used for determination of AFM1 in 29 samples of 6 different infant formula milk brands and the risk of AFM1 in infants aged zero to 6 months old was assessed using cancer risk, Margin of Exposure (MOE) and Hazard Index (HI). Only one sample (3.4%) was contaminated with AFM1. Although the results showed that MOE values for the mean and median exposure to AFM1 was <10, 000 in infants, the additional cancer risk due to mean and median exposure to AFM1 in infant <6 months were 0.00010 and 0.00012 additional cases per year per 10 5 individuals, respectively, which indicates no health concern. In addition, HI values for the mean and median exposure to AFM1 for infants were quite below one which indicates no health concern. To the best of our knowledge, this is the first report on risk assessment of AFM1 in infant formula milk consumed by Iranian infants <6 months old, presenting a low risk for the evaluated groups. Graphical abstract: Image 1 Highlights: Developing two accurate, precise, selective and sensitive methods for determining aflatoxin M1 (AFM1) in infant formula milk. Application of the methods on real infant formula milk samples. Additional cancer risk due to mean and median exposure to AFM1 in infant <6 months were 0.00010 and 0.00012 additional cases per year per 10 5 individuals, respectively. HI values for the mean and median exposure to AFM1 for infants were quite below one which indicates no health concern. Necessity of cumulative risk assessment of AFM1in infants from different provinces in IR Iran consuming infant formula milk along with milks from other sources.